Land as an indicator for national resource based policy issues - Gertel Groome, Shulamith (Družboslovne razprave, 2019)
This interdisciplinary geo-spatial overview represents a conceptual foundation for policy research concerning allocations of public commodities as represented by land (settlement) resources. Principles of collective vs. individual rights to benefit from these may pose moral dilemmas for decision-makers. Such a conflict of interests could prompt "ambiguous" governing decisions that lack clear directives for implementation. The resulting policies might support declarations of multicultural inclusivity while embracing exclusive ethnic communities. A case in point is the Israeli spatial policy on Arab and Ultra-Orthodox minority groups, analysed using primary and secondary sources and statistical data relating to political affiliations, income, housing costs and locational preferences. If land is an adequate indicator of ambiguous resource-based issues, further analyses should define how socio-spatial distributions are decided and at which particular stages of the policy process.
Keywords: Družbena geografija; družbeno-prostorski nadzor; Human geography; Naravni viri; Natural resources; prostorska neenakost; prostorska politika; Prostorska sociologija; prostorski vir; Spatial sociology